Revolting subjects: social abjection and resistance in neoliberal Britain - Tyler, Imogen (NBN International, 2013)
Revolting Subjects is a groundbreaking account of social abjection in contemporary Britain, exploring how particular groups of people are figured as revolting and how they in turn revolt against their abject subjectification. The book utilizes a number of high-profile and in-depth case studies - including 'chavs', asylum seekers, Gypsies and Travellers, and the 2011 London riots - to examine the ways in which individuals negotiate restrictive neoliberal ideologies of selfhood. In doing so, Tyler argues for a deeper psychosocial understanding of the role of representational forms in producing marginality, social exclusion and injustice, whilst also detailing how stigmatization and scapegoating are resisted through a variety of aesthetic and political strategies. Imaginative and original, Revolting Subjects introduces a range of new insights into neoliberal societies, and will be essential reading for those concerned about widening inequalities, growing social unrest and social justice in the wider global context.